Effects of RNA m6A on the formation of multi-petalization in Magnolia wufengensis: Mechanistic insights and gene expression analysis - Cunjie Li; Huarong Li; Jiang Ma; Xiaoning Fan; Yanjun Cai; Liyuan Chen; Hanlin Zhou; Hongwei Liang; Chao Zhou; Faju Chen (Horticultural Plant Journal, 2025)
N6-Methyladenosine (m6A) is the most common modification in the transcriptome of biological RNA and plays roles that include maintaining the stability and transportation of mRNA, mRNA precursor shearing, polyadenylation, and the initiation of translation. With the improving understanding of RNA methylation, m6A modification is known to play vital roles in plant development and growth. The multi-petalization of flowering plants has high ornamental and research value in horticultural landscapes. However, the mechanism of RNA methylation in flower formation in Magnolia wufengensis, a classical multi-petalizational plant, remains unclear. This study compared and analyzed RNA m6A methylation and the transcriptome in floral buds of two varieties with large differences in tepal number at the early stage of development. It was found that the degree of RNA m6A methylation and relative expression levels of MawuAGL6-2, MawuPI-4, and MawuAGL9 in ‘Jiaodan’ with 36 tepals were significantly higher than those in ‘Jiaohong’ with 9 tepals during the development of floral organ primordia. Combined with quantitative real-time PCR, the expression levels of MawuAGL6-2, MawuPI-4, and MawuAGL9 were positively correlated with the number of tepals. Transgenic experiments showed that MawuAGL6-1/2, and MawuPI-4 can increase the number of petals in Arabidopsis. Moreover, MawuAGL6-2 and MawuPI-4 can restore the missing petal phenotype of mutant Arabidopsis. Yeast two hybrid and yeast three hybrid indicated that MawuAGL6-2, MawuAP3-1/2, and MawuPI-4 could interact with each other under the mediation of the class E protein MawuAGL9. Based on these results, it is hypothesized that m6A methylation influences the multi-petalization of Magnolia wufengensis by affecting the expression levels of MawuAGL6-2, MawuAP3-1/2, MawuPI-4, and MawuAGL9. These findings provide a better understanding of the molecular mechanisms of epigenetic modifications in flower developmental diversity.